The Theme of the Shattered Self in Toni Morrison’s The Bluest Eye and A Mercy - López Ramírez, Manuela (Miscelánea: A Journal of English and American Studies, 2014)
Throughout her fiction Toni Morrison has frequently dealt with traumatized individuals, who usually belong to minority groups, especially Blacks. The fragmentation of the self and the search for identity are pervasive themes of her novels. In The Bluest Eye and A Mercy Morrison explores the passage to adulthood of two deeply traumatized teenage girls. Victimized communities or those under the threat of violence, such as primeval America, discriminate and denigrate their weakest members. Thus Pecola and Sorrow are vulnerable victims of social oppression, scapegoats. In a critical stage of their subjectivity development psychosis becomes, for these young girls, a coping strategy to survive in a hostile environment.